The Effect of Open Unemployment Rate and Average Years of Schooling (RLS) on Poverty Rate in The Province of West Nusa Tenggara 2018-2023 - Lestari, Sinta Puja; Sutanto, Himawan; Purwadinata, Subhan (West Science Social and Humanities Studies, 2025)
This study aims to examine the impact of the open unemployment rate and average years of schooling on the poverty level in West Nusa Tenggara (NTB) Province from 2018 to 2023. This research employs a quantitative approach with an associative design. Data collection was conducted directly through the Central Statistics Agency (BPS) of NTB Province. The study utilized three datasets: the poverty level indicated by the percentage of the poor population, the open unemployment rate (TPT), and the average years of schooling (RLS) in NTB Province during the specified period. The data analysis method applied in this research is panel data analysis using Eviews 12. The results indicate that the open unemployment rate has a negative and insignificant effect on the poverty level, while the average years of schooling has a negative and significant impact on poverty. Collectively, the open unemployment rate and average years of schooling significantly affect the poverty level in NTB Province from 2018 to 2023.